2016
DOI: 10.21836/pem20160304
|View full text |Cite
|
Sign up to set email alerts
|

Two administrations of an intravaginal progesterone device on the induction of ovarian cyclicity in anestrous mares

Abstract: Summary:The study aimed to evaluate the effect of double administration of a progesterone (P4) intravaginal device on induction of ovarian cyclicity in mares. Twelve crossbred mares were assigned to one of two groups. The first group (GP4; n = 6; 100 % in anestrus phase) underwent the following protocol: day (d) 0, 1.9 g of P4 + ultrasound of the uterus and ovaries (US); d 7, US; d10, first P 4 removal + US; d10 -d 24, US daily; d 28, second P4; d 35, US; d 40, second P4 removal + US; d 40 -d 54, US daily; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…PRID has been applied in mares for reversal of anoestrus (Arbeiter et al., 1994; Kaercher et al., 2013) in the transitional phase or in synchronization of oestrus and ovulation (Polo et al., 2016). After the insertion of PRID, there is the emergence of a new follicular wave, with a follicle reaching the dominance phase and resulting in ovulation, making TAI possible (Arbeiter et al., 1994; Polasek et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRID has been applied in mares for reversal of anoestrus (Arbeiter et al., 1994; Kaercher et al., 2013) in the transitional phase or in synchronization of oestrus and ovulation (Polo et al., 2016). After the insertion of PRID, there is the emergence of a new follicular wave, with a follicle reaching the dominance phase and resulting in ovulation, making TAI possible (Arbeiter et al., 1994; Polasek et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The use of PRID helps revert anoestrus and/or the transitional period in mares (Polo et al., 2016), and allows an alternative for the synchronization of ovulation. After removal of PRID, follicular follow‐up until the time of ovulation induction can take 3–8 days, and the embryo recovery rate can reach 75% in inseminated mares (Oliveira Filho et al., 2012; Polasek et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mares were resynchronized three days after the onset of synchronization with IPRD, and all mares had endometrial edema after estrogen treatment. Previous studies, treating seasonal transitional mares with IPRD to hasten cyclicity, demonstrated that mares display endometrial edema and estrus after IPRD removal [ 19 , 20 , 21 , 22 , 46 ]. In clinical practice, it is well-known that mares treated with long-acting altrenogest or LAP4 do not respond to estrogen treatment at the onset of a new synchronization protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The IPRD are typically made with a silicon matrix loaded with non-synthetic, free (non-bound) progesterone. In horses, IPRD have been used to hasten cyclicity in transitional mares, and to inhibit estrus in cyclic mares [ 19 , 20 , 21 , 22 , 23 ]. Once inserted, IPRD devices rapidly increase progesterone concentration in plasma [ 22 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A new follicular wave emerges about 3.5 to 5 days after estradiol benzoate administration (Moreno et al 2001, Bó et al 2002. The PRIDs have been used in horses in the anoestrus phase (Polo et al 2016) or the transitional phase at the beginning of the breeding season, aiming to synchronise the first ovulation, anticipating the beginning of the season (Wilde et al 2002, Handler et al 2007, Hanlon and Firth 2012.…”
Section: Introductionmentioning
confidence: 99%